INSILICO ANALYSIS ON THE EFFECT OF RUTIN BIOFLAVONOID AND CHEMOTHERAPEUTIC DRUG CYCLOPHOSPHAMIDE ON NUCLEAR FACTOR KAPPA-B PROTEIN EXPRESSION - B.REVATHI MANI; R.VENKATESWARI (International Journal of Pharma and Bio Sciences, 2014)
Cancer is medically termed as a malignant neoplasm characterized by uncontrolled growth of abnormal cells. Lung cancer is one of the commonest malignant neoplasms all over the world. Lung cancer is initiated by activation of oncogenes or inactivation of tumor suppressor genes. NF-kB p65 nuclear expression is an early and frequent phenomenon in the pathogenesis of lung cancer. It has been found that NF-kB activation plays a vital role in lung cancer pathogenesis and also identified as molecular link between inflammation and cancer. Rutin is a natural citrus bioflavonoid glycoside found in buckwheat, the leaves and petioles of Rheum species, and asparagus. The scavenging activity of rutin was strongest when compared with other flavonoids such as quercetin and naringin. The present study was undertaken to show the activity of natural therapeutic flavonoid rutin inhibiting the activity of NF-kB in lung cancer. Docking study of rutin was performed against NF-kB activity compared with the already existing chemotherapeutic agent Cyclophosphamide. The study showed a strong interaction between the rutin flavonoid with the hydrogen bonds of the NF-kB protein with a negative score inhibiting the expression of NF-kB which leads to chronic inflammation and progression of lung cancer.